2016
DOI: 10.1515/folmed-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Schizophrenia, Neurotransmitters and the New Atypical Antipsychotic Aripiprazole

Abstract: Cognition is a group of mental processes that includes the capacity to perceive, think, learn and to study, and the capacity of the brain to analyze information and program adaptive behaviour. Although there has been an appreciable evolution in the therapy of psychoses in the last twenty-five years, cognitive disturbances still persist in spite of antipsychotic treatment. The cognitive decay disrupts the ability of clinically diagnosed patients with psychoses, mainly schizophrenia, to learn and to memorize ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Preclinical studies have shown that rTMS causes complex biochemical effects and neurotropic effects by reducing inflammation and oxidative stress 33,34 . For example, studies have revealed that rTMS increases the release of dopamine in certain brain pathways 35 , which is consistent with the hypoactive dopaminergic hypothesis in cognitive deficits of patients with SCZ 36 .…”
Section: Discussionsupporting
confidence: 63%
“…Preclinical studies have shown that rTMS causes complex biochemical effects and neurotropic effects by reducing inflammation and oxidative stress 33,34 . For example, studies have revealed that rTMS increases the release of dopamine in certain brain pathways 35 , which is consistent with the hypoactive dopaminergic hypothesis in cognitive deficits of patients with SCZ 36 .…”
Section: Discussionsupporting
confidence: 63%
“…Goldberg [24] продемонстрировал, что КАП в целом оказывает умеренное благоприятное действие на когнитивные функции, в то же время доза приема препаратов не влияет на когнитивные функции, что было обнаружено и в нашем исследовании. Использование препаратов третьей генерации связывают со множеством преимуществ, в том числе и с их положительным влиянием на когнитивные функции [25].…”
Section: Discussionunclassified
“…Furthermore, ami-sulpride is considered superior to first-generation anti-psychotics for improving cognitive symptoms49) and similar to other second-generation antipsychotics for affecting all cognitive domains 50,51). In concordance, aripiprazole has been reported to improve patients’ clinical symptoms and working memory performance by acting as a partial dopamine agonist 52,53)…”
Section: Discussionmentioning
confidence: 99%